Improving iodine adsorption performance of porous organic polymers by rational decoration with nitrogen heterocycle - Wang, Yu‐Ting; An, Lian‐Cai; Zhang, Yun‐Qin; Zhang, Xin‐Kun; Gao, Zhu‐Feng; Zhang, Ying‐Hui (Journal of applied polymer science, 2021)
Four kinds of porous aminal‐linked organic polymers (PAOPs) were synthesized via one‐step condensation between cheap melamine and respective aldehydes decorated with different nitrogen heterocycle, to evaluate the influence of nitrogen heterocycle on the adsorption performance of target polymer toward iodine. Though having the smallest surface area of 209.9 m2/g, PAOP‐4 decorated with pyridine group exhibits an adsorption capacity of 108 wt% (iodine/adsorbent weight%), surpassing other three PAOPs with Brunauer–Emmett–Teller area varying from 305.8 to 533.0 m2/g. Based on Raman spectral analyses, the characteristic band of I3− and I5− was used to evaluate the electronic interaction between iodine and the nitrogen heterocycle, giving an order of pyridine > tetrazole > pyrazole > imidazole. This manifests the vital role of chemical interaction playing in the iodine adsorption by PAOP‐4, which is much helpful for designing high‐performance organic adsorbent toward iodine.